Caribbean regional health study (IDB WashingtonUS, 1996)
Seeks to provide a diagnostic summary of the major problems, issues, trends, and challenges facing the health sector in the region. Identifies key measures; feasible policy alternatives; strategies and sustainable courses of action needed to address the major constraints identified; and, to improve the overall performance of the health sector.
DC